Geochemistry of post-tectonic mafic intrusions in the Central Gneiss Terrane of southwestern Newfoundland - Currie, K.; van Berkel, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1989)
South of Grand Lake, mafic igneous complexes of proven or probable Silurian age intruded quartzofcldspathic gneisses that had been deformed and raised to granulite fades in mid-Ordovician time. The mafic igneous complexes consist of gabbroic units, which locally exhibit igneous layering and contain ul tram afic cumulate pods, that grade to and are cut by finer-grained hornblende gabbro. Compositions more felsic than diorite exhibit intrusive to co-mingling relationships with more mafic rocks. Chemical data for possible liquid-derived rocks exhibit characteristics suggesting derivation from diverse mantle sources, followed by varying combinations of fractionation, contamination, mixing and metasomatism by hydrous fluids during ascent and emplacement. The post-tectonic emplacement of the plutons suggests stabilisation of die Central Gneiss Terrane by late Ordovician or Silurian time, when the adjacent terrane to the southeast (Meelpaeg Terrane) was still undergoing deformation and granitic plutonism.